1995
DOI: 10.1002/lt.500010603
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C genotypes in liver transplant recipients: Distribution and 1-year follow-up

Abstract: Chronic hepatitis C infection (CH-C) accounts for a significant number of patients undergoing orthotopic liver transplantation (OLT). Recently, hepatitis C virus (HCV) genotype-dependent differences in disease outcome and therapeutic responses have been suggested. The objectives of our study were to determine (1) the recurrence of HCV infection after OLT; (2) distribution of HCV genotypes in patients with CH-C who required liver transplantation compared with those who did not; and (3) the 1-year transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 10 publications
(2 reference statements)
2
25
0
Order By: Relevance
“…In addition to our series, several other case reports of severe cholestatic hepatitis after receiving hearts from HCVantibody positive donors have been reported. [21][22][23][24][25] This pattern of liver injury is reminiscent of the fibrosing cholestatic hepatitis in recurrent hepatitis B virus infection 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to our series, several other case reports of severe cholestatic hepatitis after receiving hearts from HCVantibody positive donors have been reported. [21][22][23][24][25] This pattern of liver injury is reminiscent of the fibrosing cholestatic hepatitis in recurrent hepatitis B virus infection 26 …”
Section: Discussionmentioning
confidence: 99%
“…If genotype 1b is associated with more severe allograft injury, this should eventually become manifest in patient and/or graft survival. Neither the previous studies that found HCV genotype 1b to be associated with more severe chronic allograft injury [8][9][10][11][12][13] nor the Eurohep report found an association of genotype 1b with increased overall graft loss or patient mortality. The National Institute of Diabetes and Digestive and Kidney Diseases Liver Transplant Database, in a large multicenter prospective study of liver transplantation for hepatitis C, found 5-year patient graft survival to be similar among 1b and non-1b genotypes.…”
Section: Commentsmentioning
confidence: 78%
“…Previous reports of the impact of HCV genotype on outcomes in HCVinfected transplant recipients have been varied. Several groups reported that infection with HCV genotype 1b imparts an increased risk for more severe chronic allograft injury, [8][9][10][11][12][13] whereas others found no such association. [14][15][16] The basis of the heterogeneity in the results regarding the impact of HCV genotypes on the risk for more severe histological recurrence is difficult to ascertain.…”
Section: Commentsmentioning
confidence: 99%
“…39,2001 NESTED RSS-PCR FOR HEPATITIS C VIRUSresults presented above. Of the 54 strains found by RSS-PCR to have the genotype 1b pattern, 46 (85%) had 5Ј NC region sequence that was 100% identical to the corresponding 5Ј NC region sequence of prototype strain HCV-J.…”
Section: Serum Samplesmentioning
confidence: 87%
“…Amoroso et al (1) found that the rate of progression to chronic infection after acute exposure to HCV was 92% among patients who were infected with genotype 1b, whereas that rate was 33 to 50% among those infected with strains of other genotypes. Zein et al (37,39) found that genotype 1b strains occurred significantly more frequently among patients with cirrhosis and those patients requiring liver transplantation. Patients infected with genotype 1b and possibly genotype 1a may have a more unfavorable response to treatment with interferon than those infected with genotypes 2 or 3 (38).…”
Section: Discussionmentioning
confidence: 99%